SOSIALISASI URBAN FARMING MELALUI BUDIDAYA TANAMAN SAYURAN SECARA VERTIKULTUR DAN HIDROPONIK DI KELURAHAN KALIJAGA, KECAMATAN HARJAMUKTI, KOTA CIREBON - Wachdijono, Wachdijono; Wahyuni, Siti; Trisnaningsih, Umi (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2019)
Yard land in urban areas has not been utilized for the cultivation of vegetables that are productive and economically profitable. This service program aims to improve the knowledge and skills of PKK members in verticultural and hydroponic vegetable cultivation. Thus, the members can use their yard more productively. The method used in this community service program is training, which consists of counseling as well as demonstrations and practice. Counseling is about the cultivation of vegetable plants vertically and hydroponically has increased the knowledge of participants, from initially not knowing about verticulture to know. The demonstration/practice of growing vegetables the next day made the participants better understand what was delivered in the previous counseling. This encourages the improvement of mothers' skills in growing vegetables vertically and hydroponically. This additional knowledge and skills encourage participants to practice in their own homes.